Equilibria in acetone medium. VII*. Conductimetric and spectrophotometric studies on binary systems of Cobalt(II) halides with diazoles. A preliminary survey - Molina, Manuel; de Moraes, Mercedes; Melios, Cristo Bladimiros; Tognolli, João Olímpio (Eclética Química, 1979)
.